Heritage and Time Travels as a method for creating futures - Norman, Adam (2020)
The Time Travel Method is an educational method focused on addressing contemporary issues or challenges using an historical context. By placing the challenges of contemporary society in a local history setting, the method creates a safe space for reflection and dialogue, but also an understanding of historical continuity and change. The goal of the Time Travel Method is to find solutions and a common way-forward, in order to address the issues of today and to create a better future. In this article, an outline of the basic elements and mechanisms of the Time Travel Method as it has developed at Kalmar County Museum, is presented along with three practical examples on Time Travels conducted by Kalmar county museum. Resumo: O Método de Viagem no Tempo é um método educacional focado em abordar questões ou desafios contemporâneos usando um contexto histórico. Ao colocar os desafios da sociedade contemporânea em um cenário de história local, o método cria um espaço seguro para reflexão e diálogo, e também para compreensão da continuidade e mudança histórica. O objetivo do Método de Viagem no Tempo é encontrar soluções e um caminho a seguir comum, a fim de situar os problemas de hoje e criar um futuro melhor. Neste artigo, é apresentado um esboço dos elementos e mecanismos básicos do Método de Viagem no Tempo, desenvolvido no Kalmar County Museum, junto com três exemplos práticos de Viagens no Tempo conduzidas pelo Kalmar County Museum.